THE INFLUENCE OF INDIUM DOPING ON STRUCTURAL, OPTICAL AND ELECTRICAL PROPERTIES OF SnO2:IN THIN FILMS DEPOSITED BY SPRAY TECHNIQUE - BENNACEUR, K.; ATTAF, A.; SAIDI, H.; HAMANI, N.; LEHRAKI, N. (Courrier du Savoir; Vol. 24 (2017): COURRIER DU SAVOIR (Septembre), 2017)
In this present work, undoped and Indium doped tin dioxide were deposited on glass substrate by Ultrasonic spray method. We investigated the effect of deposition conditions to obtain In doped SnO2 thin films with various concentration (1 to 8 wt.%). XRD analysis confirmed that SnO2 thin films crystallize in the tetragonal structure of SnO2. The grain size average decreases with In content increase. We found that the maximum films transmittance varies from 65-93% in the visible range of the spectrum. The films optical gap varies between 3.48 and 3.80 eV. However, we have noticed that the sheet resistance increases up to 880*103 (Ω/sqr) with increasing the in doping concentration. Owing to their high optical gap and high sheet resistance; the prepared films can be employed in optoelectronic devices.